2019
DOI: 10.3892/ol.2019.9928
|View full text |Cite
|
Sign up to set email alerts
|

Dark‑colored maple syrup treatment induces S‑phase cell cycle arrest via reduced proliferating cell nuclear antigen expression in colorectal cancer cells

Abstract: Maple syrup is a natural sweetener that is consumed worldwide. It has been previously reported that dark-colored maple syrup exerts an inhibitory effect on colorectal cancer (CRC) proliferation and invasion. In the present study, the underlying mechanism of CRC cell growth inhibition was examined with dark-colored maple syrup treatment using a shotgun liquid chromatography-tandem mass spectrometry-based global proteomic approach. Applying a semi-quantitative method based on spectral counting, 388 proteins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…in the present study, rom-1 levels were lower in the retinas of STZ rats than normal rats. as the results of semi-quantitative analysis based on spectral counts highly correlate with the results of quantification by Western blot in previous studies (12,45,46), the expression of Table V. Proteins categorized as 'protein binding' in Gene ontology analysis.…”
Section: Discussionsupporting
confidence: 68%
“…in the present study, rom-1 levels were lower in the retinas of STZ rats than normal rats. as the results of semi-quantitative analysis based on spectral counts highly correlate with the results of quantification by Western blot in previous studies (12,45,46), the expression of Table V. Proteins categorized as 'protein binding' in Gene ontology analysis.…”
Section: Discussionsupporting
confidence: 68%
“…This suggested that autophagy was induced to protect cancer cells against MSpf treatment. Since inhibition of the STAT3 signaling pathway is associated with not only induction of autophagy but also induction of apoptosis and cell cycle arrest ( 55 57 ), in addition to our previous study showing that maple syrup treatment induces S-phase cell cycle arrest ( 14 ), AGEs in MSpf may have induced cell cycle arrest.…”
Section: Discussionmentioning
confidence: 84%
“…Maple syrup is a better alternative to refined sugar in the human diet owing to its low glycemic and insulinemic response properties (11,12). In addition, it was previously reported that maple syrup has an anti-tumor effect against gastrointestinal cancer cells, including CRC (13)(14)(15). Therefore, maple syrup may be a useful resource to investigate phytochemicals for CRC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As the season progresses, maple syrup’s color darkens, and it is classified into four grades: golden, amber, dark, and very dark [ 1 ]. Maple syrup has various biological effects, and it has also been reported that different grades of maple syrup could have different biological effects [ 2 , 3 , 4 , 5 , 6 ]. Although maple syrup has a low glycemic index (GI), it is mostly sucrose with a small amount of glucose and fructose [ 5 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%